TASHQI IQTISODIY FAOLIYATNI MAMLAKATIMIZDA YANADA TAKOMILLASHTIRISH - Misirov Asliddin; Suyunova Sevinch Lutfullayevna (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract. This article analyzes the state of foreign economic activity of the Republic of Uzbekistan and provides proposals and recommendations for its further development and improvement. The issues of integration with the world economy, increasing export potential, attracting foreign investments, and stimulating foreign economic activity through improving the system of customs and tax incentives are covered. Also, the article, based on the analysis of existing problems, considers the directions of liberalization of foreign trade policy and production of competitive products.